Usando a Entropia de Transferência para medir o fluxo de informações nas séries de preços de açúcar, etanol e petróleo bruto - da Silva, Joelma Mayara; Gonçalves Ferreira, Mirelly; de Carvalho Barreto, Íkaro Daniel; Stosic, Tatijana; Stosic, Borko (Sigmae, 2019)
In the last years the ethanol production was grown up in the entire world, which also occurred in the Brazil, the second world production, the Brazilian product is classified was biofuel and derivate the sugarcane, it is also raw material of sugar. Furthermore, studies stand the influence in fuels from the foods prices, because the increase fuels prices increase the cost of transport and consequently the food production. On this, we study the direction of information flow between Brazilian ethanol and sugar prices and international crude oil prices using the Transfer entropy method. We find stronger information transfer from crude oil to sugar and crude oil to ethanol for return and volatility series while for original series the net information transfer was in opposite direction. There was no net information transfer between ethanol and sugar series, indicating that Brazilian biofuel and agricultural market are strongly related with international crude oil market.